Whole-Genome Sequencing Analysis of Quorum-Sensing Aeromonas hydrophila Strain M023 from Freshwater - Tan, Wen Si; Yin, Wai Fong; Chang, Chien Yi; Chan, Kok Gan (American Society for Microbiology, 2015)
Aeromonas hydrophila is a well-known waterborne pathogen that recently was found to infect humans. Here, we report the draft genome of a freshwater isolate from a Malaysian waterfall, A. hydrophila strain M023, which portrays N-acylhomoserine lactone-dependent quorum sensing.